M.A.R.V.E.L.S. "Medical Students Advancing Research, Visibility, Education, Leadership, and Support." A Student-Driven Initiative - Molly Mehta; Kayvon Yazdanbakhsh; Elizabeth Hsu; Olga Gomeniouk; Kayla Nenninger; Devin P. Asher (International Journal of Medical Students, 2025)
BACKGROUND: Research activity is crucial for medical students' professional growth and development. However, significant barriers to accessing research opportunities remain. We introduce a student-led initiative designed to improve research accessibility and training for medical students while creating advancement opportunities for student researchers in their respective fields. AIMS: 1. Foster peer guidance in medicine to make research accessible to all students regardless of gender, experience, and specialty interests 2. Create student research training that integrates with medical school curricula 3. Facilitate ongoing communication regarding the current research and scholarly activities at our institution.